2018
DOI: 10.2147/cpaa.s171735
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I, open-label, randomized, crossover study in healthy subjects to evaluate the bioavailability of, and the food effect on, a pomalidomide oral liquid suspension

Abstract: ObjectiveThe aim of this study was to evaluate the bioavailability of a pomalidomide oral liquid suspension relative to the commercial capsule formulation and to assess the food effect on the pomalidomide oral liquid suspension when administered as a single 4 mg dose.MethodsThis was an open-label, randomized, three-period, two-sequence crossover study in healthy subjects consisting of a screening phase, a baseline assessment phase, a treatment phase with three periods, and a follow-up phone call phase. Blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…22 A food effect bioavailability study conducted on a POM capsule formulation revealed that the coadministration of POM with high-fat and high-calorie meals delayed t max by 2.5 hours, and that it decreased mean plasma C max and AUC in healthy volunteers by ≈27% and 8%, respectively. 12 These results are consistent with the findings of the present study. Therefore, it can be concluded from this analysis that the mild to moderate differences in AUC and C max observed when POM capsules (4 mg) were administered with food do not appear to influence their efficacy or safety profiles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…22 A food effect bioavailability study conducted on a POM capsule formulation revealed that the coadministration of POM with high-fat and high-calorie meals delayed t max by 2.5 hours, and that it decreased mean plasma C max and AUC in healthy volunteers by ≈27% and 8%, respectively. 12 These results are consistent with the findings of the present study. Therefore, it can be concluded from this analysis that the mild to moderate differences in AUC and C max observed when POM capsules (4 mg) were administered with food do not appear to influence their efficacy or safety profiles.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, POM can be administered with or without food. 12 POM was extensively metabolized (primarily by cytochrome P450 [CYP] 1A2 and CYP3A4, and secondarily by CYP2C19 and CYP2D6), and is still the main circulating component (accounting for ≈70% of circulating radioactivity). [13][14][15] A single dose of 4-mg POM was safe and well tolerated by male subjects with severe, moderate, or mild liver injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is critical to characterize the bioavailability (BA), or the bioequivalence (BE), of medications with different formulations in medicine and pharmaceutical development, as per the global regulatory requirement. 17 FDA guidance of BA and BE studies for orally administered drug products indicates that studies to measure BA and/ or establish BE of a product are important elements in support of investigational new drugs (INDs), new drug applications (NDAs), abbreviated new drug applications (ANDAs) and their supplements. 18,19 In line with the guidance, the study herein was aimed to evaluate the BA of two newly developed formulation (P01-TAB and P22-CAP) relative to the reference formulation (P01-CAP).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigated compounds acting on the innate immune system (19 studies) (20-38), followed by compounds w i t h i m m u n o r e g u l a t o r y a c t i v i t y , c l a s s i fi e d i n t o immunomodulatory (cereblon [CRBN] modulators; 14 studies) (39)(40)(41)(42)(43)(44)(46)(47)(48)(49)(50)(51)(52) and mediators of immune cell functions (CCR5 antagonists; 14 studies) (54-59, 61-63, 65-67, 76). All the other compounds were investigated in only one or two HV studies.…”
Section: Compounds Tested In Healthy Volunteersmentioning
confidence: 99%